A survey of qualitative spatial representations. (17th October 2013) - Chen, Juan; Cohn, Anthony G.; Liu, Dayou; Wang, Shengsheng; Ouyang, Jihong; Yu, Qiangyuan
Abstract Representation and reasoning with qualitative spatial relations is an important problem in artificial intelligence and has wide applications in the fields of geographic information system, computer vision, autonomous robot navigation, natural language understanding, spatial databases and so on. The reasons for this interest in using qualitative spatial relations include cognitive comprehensibility, efficiency and computational facility. This paper summarizes progress in qualitative spatial representation by describing key calculi representing different types of spatial relationships. The paper concludes with a discussion of current research and glimpse of future work.